The natural history of pregnancy-related enhanced myometrial vascularity following miscarriage - Grewal,K; Al-Memar,M; Fourie,H; Stalder,C; Timmerman,D; Bourne,T (Ultrasound in Obstetrics and Gynecology, 2020)
OBJECTIVES: Our primary aim was to report the incidence of enhanced myometrial vascularity (EMV) in consecutive women following first trimester miscarriage who attended our early pregnancy assessment unit. We further aimed to evaluate the clinical presentation, and complications associated with the condition. METHODS: A prospective cohort study conducted in a London teaching hospital between June 2015 and June 2018. Consecutive patients with an observation of EMV by transvaginal ultrasonography (TVS) were included. The diagnosis was made following the subjective identification of EMV using color Doppler ultrasonography and a peak systolic velocity (PSV) ≥20cm/sec within the collection of vessels. Women were followed up with repeat scans every 14 days. Management was expectant unless intervention was indicated because of excessive or prolonged bleeding, the persistent presence of retained tissue in the endometrial cavity or patient choice. The final clinical outcome was recorded. Time to resolution was defined as the date of EMV detection until resolution was observed. The time to cessation of symptoms was also documented. RESULTS: Forty patients were diagnosed with EMV during the study period following miscarriage and included in the study. There were 2627 first trimester losses in the department during this study period, hence the incidence of EMV following miscarriage was 1.52%. All cases were associated with ultrasound evidence of retained products of conception (RPOC) at presentation (mean dimensions 22x20x20mm). Thirty-one patients initially opted for expectant management, of which 18 were successful, five were lost to follow up and eight subsequently had surgical evacuation due to patient wishes. No expectantly managed case required emergency intervention. Nine patients chose surgical evacuation as primary treatment. No strong correlation was seen between PSV and blood loss at surgery (PSV range 20-148cm/sec, median 47 cm/sec). The estimated blood lo